¿Caminos intrincados?. La narrativa de Vargas Llosa y las ciencias sociales - Plasencia Soto, Rommel (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Article that makes an introduction to four texts by Mario Vargas Llosa from the social sciencies and the inevitable comparison with the literature post-indigenist of José María Arguedas, Linkwise is emphatized that the literally production of these two novelist seen like antipodal of the modern peruvian narrative, actually brought together as two rebellions attitudes before the modernity in that one to mark the aggression to the individual freedom and of other one, the dear of the dissolution of our cultural forms.